(untitled) (National Administration Journal, 2020)
Social responsibility is assumed as a voluntary commitment of companies to ensure economic, social and environmentally responsible growth for which it is necessary to determine the perception of entrepreneurs regarding accountability for their economic activities. This study is framed within the qualitative and quantitative modality, applying theoretical level methods, for the diagnosis to several companies in the province of Imbabura-Ecuador. The survey technique is used in relation to the perception of entrepreneurs. As a result, it is noted that there is not enough commitment regarding accountability.